CSR Accounting 'New Wave' Researchers: 'Step Up to The Plate'… Or 'Stay Out of The Game' - Charles H. Cho (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Recent discussions at accounting conferences and workshops suggest that academics are 'deeply divided' on the role and purpose of corporate social responsibility (CSR) accounting. This 'rift' has been created by moves from mainstream accounting researchers to contribute to a body of evidence that is almost 50 years old without—many believe—being cognizant, or even respectful, of the work that has gone before. The existing work by CSR accounting scholars puts sustainability of the planet at its core, rejecting narrow or instrumental approaches to the fundamental issues; in contrast, more recent 'capital market-based' work takes investor-centric, or market-driven approaches to 'sustainability' and CSR. While there are calls for greater understanding of, and empathy for, each other's views and perspectives, this essay identifies some particular pain-points, and calls for new wave researchers—those who recently '(re)discovered' CSR accounting research—to 'step up (to their plate)' or simply 'stay in their own lane (or, out of the game)'.
Keywords: M41; M14; 650; corporate social responsibility (CSR); CSR accounting research; sustainability; CSEAR; bibliography; mainstream; 'new wave'